2018
DOI: 10.1016/j.jff.2018.05.069
|View full text |Cite
|
Sign up to set email alerts
|

GPETAFLR, a novel bioactive peptide from Lupinus angustifolius L. protein hydrolysate, reduces osteoclastogenesis

Abstract: 26The effect of GPETAFLR, a peptide isolated from Lupinus angustifolius L. 27 protein hydrolysate (LPH), on osteoclastogenesis was investigated. Human 28 osteoclasts generated from monocytes were used to analyse the effects of 29 GPETAFLR (50-100 µg/mL) on osteoclastogenesis using TRAP reaction, RT-30 qPCR, and ELISA procedures. LPS enhanced TRAP activity and the expression 31 of osteoclast marker genes (TRAP, OSCAR, RANK, and CATHK) while 32 downregulated the expression of OPG gene in human monocyte-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Researchers found that buckwheat extracts may inhibit adipogenesis and inflammatory response during adipocyte differentiation of 3T3‐L1 cells.22 Brazilian red propolis ( Apis mellifera ), Copaifera oleoresins, flavonoid fraction of Bergamot Juice ( Citrus bergamia ), effusanin C ( Isodon japonicus ), oligomeric proanthocyanidins ( crataegus oxyacantha ) are others isolated compounds with anti‐inflammatory actions in activated monocytes and macrophages (Montserrat‐de la Paz et al, ). As well as prior studies (Millan‐Linares et al, , ), showing GPETAFLR as one of the major bioactive peptides with anti‐inflammatory activity, our observations suggest that this octapeptide isolated from Lupinus angustifolius L . is associated with a remarkable prevention of oxidative and inflammatory in RPE cells.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Researchers found that buckwheat extracts may inhibit adipogenesis and inflammatory response during adipocyte differentiation of 3T3‐L1 cells.22 Brazilian red propolis ( Apis mellifera ), Copaifera oleoresins, flavonoid fraction of Bergamot Juice ( Citrus bergamia ), effusanin C ( Isodon japonicus ), oligomeric proanthocyanidins ( crataegus oxyacantha ) are others isolated compounds with anti‐inflammatory actions in activated monocytes and macrophages (Montserrat‐de la Paz et al, ). As well as prior studies (Millan‐Linares et al, , ), showing GPETAFLR as one of the major bioactive peptides with anti‐inflammatory activity, our observations suggest that this octapeptide isolated from Lupinus angustifolius L . is associated with a remarkable prevention of oxidative and inflammatory in RPE cells.…”
Section: Resultssupporting
confidence: 90%
“…Considering the MTT assay, 50 and 100 μg/ml of peptide showed more than 98% viability of the cells. In previous reports, GPETAFLR were not cytotoxic to primary human monocytes (Montserrat‐de la Paz et al, ), human monocyte‐derived osteoclasts (Millan‐Linares et al, ), and THP‐1 cells (Millan‐Linares et al, ) at the same concentrations.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Its immunomodulatory and anti-inflammatory capacities have been demonstrated. 11 Its effects have been previously investigated in macrophage THP-1-line derivatives, 11 osteoclasts derived from human primary monocytes, 12 and primary human monocytes. 13 Hence, it is an interesting compound to treat or prevent diseases characterized by inflammation.…”
Section: Introductionmentioning
confidence: 99%